Curriculum kardiale Computertomographie - Schmermund, A.; Achenbach, Susanne; Leber, A.; Strasser, R. H.; Korosoglou, G.; Hausleiter, J.; Voigtländer, T.; Katus, H. A. (Der Kardiologe, 2015)
The curriculum presented describes a structured process of further education allowing cardiologists to obtain an additional qualification in cardiac computed tomography (CT). The additional qualification is defined by the German Cardiac Society and certified according to uniform criteria. Three levels of education are associated with increasing degrees of qualification. Level 1 mainly pertains to CT indications, diagnostic value and comparisons with alternative diagnostic methods, level 2 adds further competence in cardiac CT, enabling independent performance of cardiac CT examinations and level 3 allows cardiologists to operate a cardiac CT imaging unit in their own right, under the premise of radiation safety rules being observed and to oversee the education of candidates for additional cardiac CT qualifications. Apart from individual education the process of certifying training centres is also described and examination of the candidates for additional CT qualifications. The current curriculum takes the curriculum for further cardiological education of the German Cardiac Society into consideration as well as national and European consensus recommendations on cardiovascular imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Advanced training; Certification; Coronary angiography; Tomographic imaging; Training